Case reportsA young woman with Takayasu arteritis: surgical and anesthetic management of Bentall procedure in a patient with abdominal aortic aneurysm and renal artery stenosis - Baysal, Ayse; Rabus, Murat Bulent; Alsalehi, Saleh; Gul, Yasar; Kocak, Tuncer; Balkanay, Mehmet (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Takayasu’s arteritis (TA) is a rare form of chronic vasculitis involving large arteries. We present the case of a 19-year-old female patient diagnosed with TA, whose medical treatment lasted a period of twelve months. The patient was admitted due to aortic regurgitation and enlargement of the aorta up to 6 cm. Her biochemical laboratory data were normal. Angiographic studies showed occlusive disease as well as aneurysms in the abdominal aorta and left renal artery, which are considered to be significant sources of postoperative complications. Hemodynamic parameters were well regulated throughout the surgery. No complications were recorded. Surgery for TA should be deferred during the active phase of the disease due to increased bleeding, friable tissue, and increased risk of thrombosis. Appropriate medical treatment before and during surgery is required to perform a successful surgical procedure without the development of postoperative complications.